Photosynthetic UV stress tolerance of the Antarctic snow alga Chlorella sp. modified by enhanced temperature? - Rivas, C.; Navarro Martinez, Nelso Patricio; Huovinen, P.; Gómez, I. (My University, 2016)
BACKGROUND: Photosynthetic characteristics and the effect of UV radiation and elevated temperature measured were studied in Chlorella sp. isolated from a snow microalgal community at King George Island, Maritime Antarctica through the chlorophyll florescence (rapid light curves and maximum quantum yield, respectively). The environmental context was monitored through measurements of spectral depth profiles of solar radiation (down to 40 cm) in the snowpack as well as a through continuous recording of temperature and PAR using dataloggers located at different depths (0-30 cm) within the snow column RESULTS: The photochemistry of Chlorella sp. was affected by UV radiation in a 12-h laboratory exposure under all studied temperatures (5, 10, 15, 20 °C): the algae exposed to PAR + UV-A radiation were inhibited by 5.8 % whilst PAR + UV-A + UV-B radiation decreased Fv/Fm by 15.8 %. In both treatments the 12-h recovery after UV exposure was almost complete (80-100 %). Electron transport based P-I curve parameters maximal electron transport rate (ETRmax), photosynthetic efficiency (α) and the saturating irradiance (Ek) no varied in response to different temperatures CONCLUSIONS: Results revealed that Chlorella sp. not only shows high photosynthetic efficiency at ambient conditions, but also exhibits tolerance to solar radiation under higher temperatures and possessing a capacity for recovery after inhibition of photosynthesis by UV radiation
Keywords: antarctica; snow algae; chlorella sp; photosynthesis; uv radiation; temperature